HIV/AIDS Related KAP Among High-School Students of Municipal Corporation School in Pune - An Interventional Study - Gupta, Pankaj Kumar; Pore, Prasad; Patil, Usha (National Journal of Community Medicine, 2012)
Background: Adolescents form substantial risk group due to situations arising out of their curiosity, haphazard knowledge, and risk-prone behavior. Present study was planned with an objective to assess knowledge, attitude about HIV/AIDS in adolescents. Methodology: The study was conducted in a school of field practice area of Urban Health Training Center. Pre-designed, pre-tested anonymous, self administered questionnaire was filled by 9th standard students after obtaining necessary permission. A film on HIV/AIDS was shown to them. The same questionnaire was again filled by the students. Results: Sixty three percent students were aware about HIV/AIDS. TV was the main source of information. A significant decrease in knowledge about misconceptions and significant increase in knowledge occurred about various modes of transmission of disease, prevention of HIV/AIDS in post testing. Conclusion: Intervention in the form of a film even can make a significant change in knowledge and attitude of adolescents going to school.